Localism and police governance in England & Wales: Exploring continuity and change. (September 2019) - Jones, Trevor; Lister, Stuart
This article develops further criminological understandings of 'localism' in police governance and contributes to broader theoretical discussions about 'governance' in contemporary policing, via a critical analysis of major recent law and policy reforms in England & Wales. Recent legislation has brought important changes to the balance of constitutional-legal powers and the institutional architecture of police governance. However, we argue that for several reasons it is problematic to interpret these developments in straightforward terms of greater 'localization'. First, in so far as there has been a decentralization of control, this represents a growth of 'regional' rather than 'local' auspices of power. Second, there is widespread evidence of continuing interventionism by 'the centre', asserting strong influences on local policing via a range of national bodies. Third, important developments in the wider context of police policy-making – most importantly the conditions of austerity – have circumscribed the capacity of Commissioners to set their own policy agendas and resulted in a retrenchment of policing provision at the most 'localized' geographical units of neighbourhoods. Indeed, the combination of decentralizing formal responsibility for policing policy and restrictive central financial controls amounts in practice to a 'devolution of blame' by the centre for falling service standards. Finally, we argue that the growing complexity and fragmentation of police governance cannot be captured adequately by 'vertical' analysis of central–local relations. Although central influences remain predominant, policing policy networks have become more diverse, with important developments at 'horizontal' levels locally, regionally and nationally. Within this more fragmented governance framework, central influences continue to drive local policing, but primarily via a range of 'arm's length' institutions and techniques.